2015
DOI: 10.1016/j.ntt.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic, bioenergetic, and behavioral effects of exposure to total particulate matter on early development of zebrafish (Danio rerio) are not mimicked by nicotine

Abstract: Cigarette smoke has been associated with a number of pathologies; however, the mechanisms leading to developmental effects are yet to be fully understood. The zebrafish embryo is regarded as a ‘bridge model’; however, not many studies examined its applicability to cigarette smoke toxicity. This study examined the effects of total particulate matter (TPM) from 3R4F reference cigarettes on the early development of zebrafish (Danio rerio). Zebrafish embryos were exposed to two concentrations of TPM (0.4 and 1.4 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…Specifically, oxidative stress induction is supported by an increased ratio of GSSG to TGSH (or GSH), or a decreased ratio of TGSH (or GSH) to GSSG. While only four of the aforementioned zebrafish studies reported the ratios, the ratios supported the induction of oxidative stress in all four studies by Arnold et al (2016), Jaja-Chimedza et al (2012), and Massarsky et al (2013; 2015). Notably, the studies by Massarsky et al (2013; 2015) and Arnold et al (2016) used the methods described in the present manuscript.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Specifically, oxidative stress induction is supported by an increased ratio of GSSG to TGSH (or GSH), or a decreased ratio of TGSH (or GSH) to GSSG. While only four of the aforementioned zebrafish studies reported the ratios, the ratios supported the induction of oxidative stress in all four studies by Arnold et al (2016), Jaja-Chimedza et al (2012), and Massarsky et al (2013; 2015). Notably, the studies by Massarsky et al (2013; 2015) and Arnold et al (2016) used the methods described in the present manuscript.…”
Section: Discussionmentioning
confidence: 50%
“…In the studies reporting decreased GSH concentration, the concentration of GSSG was increased (Liu et al, 2015 - PCB 126), not significantly affected (Massarsky et al, 2013 – silver nanoparticles; Arnold et al, 2016 – selenomethionine), or decreased (Wu et al, 2011 - bisphenol A and nonylphenol). In the studies reporting increased GSH concentration, the concentration of GSSG was not significantly affected (Jaja-Chimedza et al, 2012 - bacterial lipopolysaccharides) or increased (Massarsky et al, 2015 – total particulate matter). It is noteworthy that the methods described herein allow for the concentrations of GSH and GSSG to be derived from the same sample, which is efficient in terms of cost, reagents, and time.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations